136 Field-Steering Rescue Lead Therapy for Patients With Essential Tremor Refractory to Ventralis Intermedius Deep Brain Stimulation. (August 2016) - Sukul, Vishad; Isaacs, David A.; Pallavaram, Srivatsan; Rodriguez, William; Butler, Jonathan; Yu, Hong; Neimat, Joseph Samir; Konrad, Peter
Abstract : INTRODUCTION: Nucleus ventralis intermedius (VIM) deep brain stimulation (DBS) is an effective therapy for the treatment of refractory essential tremor (ET). Therapy may fail in as many as 9% of patients despite positive initial results. In cases where good placement has been confirmed, evidence suggests that anterior adjacent lead placement can improve symptoms. We describe our cumulative surgical experience. METHODS: A total of 6 patients were reviewed retrospectively. These patients had a second DBS array placed after programming failed to recapture initial tremor control. Additional leads were implanted with the intent of steering the field anteriorly to recapture tremor control in the motor thalamus, targeting a location 4 to 6 mm anteromedial from the original VIM lead. Clinical, anatomic, and intraoperative data were postprocessed with respect to a probabilistic atlas. RESULTS: A total of 9 leads were implanted in 6 patients (3 bilateral, 3 unilateral). Original leads plotted into the atlas overlaps with the normalized efficacy map predicting good initial tremor capture relative to the cumulative ET population. Time to secondary implant was 2.68 ± 1.38 years with the exception of 1 outlier at 11 years. New leads were placed on average 4 to 6 mm anteromedially, and programmed to allow for driving of the current between the 2 leads. Rescue of tremor control was demonstrated in all patients based on clinical evaluation, but programming voltage changes varied widely. A descriptive electric field diagram was also modeled. CONCLUSION: Rescue lead therapy shows clinical benefit for tremor control in VIM refractory ET patients. There is debate regarding why this occurs-electrical tolerance vs physiologic "escape" from capture by a single array lead. However, our results suggest that failed control with previously successful single-array implants can be rescued by a second anterior array implant. Further investigation is ongoing and will allow us to further understand this therapeutic option.